PENGEMBANGAN PROGRAM BOARDING SCHOOL DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK DI MADRASAH - Jannati Aliyah; Fajri Ismail; Muhammad Win Afgani (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Boarding school is a school system with dormitories where students as well as teachers and school managers live in dormitories within the school environment for a certain period of time, in the Boarding School education system all students are required to live in one dormitory. Therefore, teachers or educators it is easier to control the development of the character of students in curricular and extracurricular activities, both in boarding schools and the community environment monitored by teachers for 24 hours. with a load of ieval values. This Elisan uses the library research method by using analysis and in-depth analysis of relevant library materials in books and journals that Jayak used as a reference in making this analysis. The data collection technique used in this paper uses secondary data, namely by collecting data indirectly by examining the chicks in question. This paper aims to describe and investigate more deeply about Boarding Schools that practice waiting for Boarding Schools, the characteristics of the Boarding School learning system, the benefits of using Bearing. School, and the Manzan Boureling.chool program in building character in madrasas.